Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1074/jbc.m508678200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Hydrophobic Residue as a Key Determinant of Fructose Transport by the Facilitative Hexose Transporter SLC2A7 (GLUT7)

Abstract: Until recently, the only facilitated hexose transporter GLUT proteins (SLC2A) known to transport fructose were GLUTs 2 and 5. However, the recently cloned GLUT7 can also transport fructose as well as glucose. Comparison of sequence alignments indicated that GLUTs 2, 5, and 7 all had an isoleucine residue at position "314" (GLUT7), whereas the non-fructose-transporting isoforms, GLUTs 1, 3, and 4, had a valine at this position. Mutation of Ile-314 to a valine in GLUT7 resulted in a loss of fructose transport, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 28 publications
6
47
1
Order By: Relevance
“…Exposure of cells expressing a single Cys-substituted form of GLUT1 to a water-soluble sulfhydryl reagent revealed that the exofacial portion of TM7 is accessible to the external solvent (19). A QLS motif present in TM7 of GLUT family proteins has been proposed to interact with the C-1 position of D-glucose (20), and Ile 314 situated at the outer edge of TM7 of GLUT7 was shown to be required for fructose transport (21). Studies of other MFS transporters have also shown the importance of TM7.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure of cells expressing a single Cys-substituted form of GLUT1 to a water-soluble sulfhydryl reagent revealed that the exofacial portion of TM7 is accessible to the external solvent (19). A QLS motif present in TM7 of GLUT family proteins has been proposed to interact with the C-1 position of D-glucose (20), and Ile 314 situated at the outer edge of TM7 of GLUT7 was shown to be required for fructose transport (21). Studies of other MFS transporters have also shown the importance of TM7.…”
Section: Resultsmentioning
confidence: 99%
“…Fructose is transported passively across membranes by a member of the facilitative glucose transporter (GLUT) family, named GLUT5 (60)(61)(62)(63)(64) and it is the sole transporter specific for fructose with no ability to transport glucose or galactose. The low intracellular fructose concentration is possible because fructose is metabolized and significantly contributes to glycogenolysis in muscle or lipogenesis in adipocytes (63,65).…”
Section: Discussionmentioning
confidence: 99%
“…59 It was speculated that this residue was facing the aqueous pore at the exofacial vestibule of GLUT7 using a computer model of the GLUT7 protein based on the GlpT crystal structure. 60 However, analysis using a GLUT9 computer model based on the recent GLUT1 crystal structure indicates that this isoleucine is more likely to be facing away from the aqueous pore and to be acting as a structural regulator through hydrophobic interactions with adjacent TMs. 61 At the equivalent position in Class I GLUTs (except for GLUT2 which can also transport fructose) there is a valine residue.…”
Section: Class II Glutsmentioning
confidence: 99%